Dynamic Contrast-Enhanced MRI Confirms Rapid And Sustained Improvement Of Rheumatoid Arthritis Induced By Tocilizumab Treatment: An Italian Multicentre Study - Cimmino MA (Dove Medical Press, 2020)
Marco A Cimmino,1 Massimiliano Parodi,1 Francesca Barbieri,1 Stefano Bombardieri,2 Giuseppe Zampogna,1 Annamaria Iagnocco,3 Alberto Batticciotto,4 Luca Maria Sconfienza,5,6 Luigi Sinigaglia,7 Fabrizio De Benedetti,8 Fabiola Atzeni,9 Piercarlo Sarzi-Puttini10 1Research Laboratory and Academic Division of Clinical Rheumatology, Department of Internal Medicine, University of Genoa, Genoa, Italy; 2Rheumatology Unit, Santa Chiara Hospital, University of Pisa, Pisa, Italy; 3Academic Rheumatology Centre, Università degli Studi di Torino, Turin, Italy; 4Rheumatology Unit ASST-Settelaghi, Ospedale di Circolo – Fondazione Macchi, Varese, Varese, Italy; 5IRCCS Istituto Ortopedico Galeazzi, Milan, Italy; 6Dipartimento di Scienze Biomediche per la Salute, Università degli Studi di Milano, Milan, Italy; 7Rheumatology Unit, G. Pini Hospital, Milan, Italy; 8Division of Rheumatology, IRCCS, Bambin Gesù Paediatric Hospital, Rome, Italy; 9Rheumatology Unit, University of Messina, Messina, Italy; 10Rheumatology Unit, L. Sacco University Hospital, Milan, ItalyCorrespondence: Piercarlo Sarzi-PuttiniReumatology Department, L. Sacco University Hospital, ASST Fatebenefratelli – Sacco, Via G.B. Grassi, 74, Milan 20157, ItalyTel +39 02 39042208Email piercarlo.sarziputtini@gmail.comObjective: This open-label study evaluated the effects of combined tocilizumab (TCZ) and disease-modifying antirheumatic drugs (DMARDs) on magnetic resonance imaging (MRI) changes in synovial membrane enhancement, bone marrow edema (BME), and erosions in the wrist and hand joints of rheumatoid arthritis (RA) patients inadequately responding to DMARDs alone.Methods: The efficacy of intravenous TCZ 8 mg/kg administered every four weeks for 48 weeks was evaluated on six occasions. The primary endpoints were the changes in the extent and degree of wrist synovitis as measured using the RA MRI Score (RAMRIS) and dynamic, gadolinium-enhanced 0.2T MRI (DCE-MRI). A number of different parameters of DCE-MRI were evaluated.Results: Fifty-eight patients were treated, eight of whom (13.8%) discontinued the study prematurely. The mean RAMRIS significantly decreased after two weeks and the decrease was maintained for up to 48 weeks. By week 4, the mean RAMRIS synovitis score had significantly decreased from baseline (− 0.804± 1.575; p=0.018), but not the mean early enhancement (REE) or relative enhancement (RE). However, there were significant decreases in RE at week 24, in REE and Ntotal (total number of enhancing voxels)*IRE (initial rate of enhancement) at weeks 12, 24 and 48, and in Ntotal*ME (maximal enhancement) at weeks 24 and 48. Mean BME decreased from baseline to week 48, and bone erosions did not progress. The patients’ clinical parameters significantly improved from baseline until week 48.Conclusion: TCZ in combination with DMARDs improved wrist synovitis, BME and clinical parameters, without any progression in bone erosions. The RAMRIS for synovitis rapidly improved from as early as two weeks after the first TCZ infusion. (Funded by F. Hoffmann–La Roche; ACTRACE EudraCT No. 2009 012185-32).Keywords: tocilizumab, rheumatoid arthritis, wrist, synovitis, low-field MRI, dedicated MRI